Analyzing the patterns of travel behavior of Jessore City - Rahaman, Khan Rubayet; Ahmad, Fazle Rabbi Ashik (Revista Brasileira de Gestão Urbana, 2017)
The purpose of this paper is to examine what is known about travel behavior and analyzing the existing pattern of travel behavior of Jessore City. In Jessore City about 83% trips are home based. There are a large number of decisions that people make about their travel behavior, such as their destinations, the mode (car or bus, for example), the time of day they travel, organizing individual trips into chains, and so on. In addition, broader factors such as population, economic growth, and technological changes can impact travel decisions. In this study several spatial or geographical factors, like the local service accessibility, have been studied in order to explain the differences in travel patterns. It is found that once monthly household income increased, the number of home-based trips per household per day also increased. Among the different mode of travel available in Jessore City, rickshaw (tri cycle human hauler) is the most popular and easily available mode of travel. The study also tries to define how local factors – so called spatial factors – affect the travel behavior. The basic hypothesis is that in Jessore City, where the local service level is low and distances to service areas are long, the number of daily trips is smaller.